Pain Characteristics of Adults 65 Years of Age and Older Referred to a Tertiary Care Pain Clinic - Angela Mailis-Gagnon; Keith Nicholson; Balaji Yegneswaran; Mateusz Zurowski (Pain Research and Management)
BACKGROUND: Reports indicate that characteristics of older adults with chronic pain may be different than those of younger persons.